2018
DOI: 10.1002/jbmr.3479
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Bone Resorption by miR-141 in Aged Rhesus Monkeys

Abstract: Aging-related osteoporosis (OP) is considered a serious public health concern. Approximately 30% of postmenopausal women suffer from OP; more than 40% of them risk fragility fractures. Multiple drugs have been prescribed to treat OP, but they are not ideal because of low cure rates and adverse side effects. miRNA-based gene therapy is a rapidly developing strategy in disease treatment that presents certain advantages, such as large-scale production capability, genetic safety, and rapid effects. miRNA drugs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…miR-141 has been identified as a quintessential negative inhibitor of osteoclastogenesis and bone resorption. The functional mechanism involves its targeting of two osteoclast differentiation factors, calcitonin receptor (Calcr) and ephrin A receptor 2 precursor (EphA2) [84]. Recent experiments have shown that oleanolic acid, a new drug that can be used to treat osteoporosis, inhibits RANKL-induced osteoclastogenesis through the ERα/ miR-503/RANK signaling pathway in RAW264.7 cells [85].…”
Section: Microrna-mediated Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-141 has been identified as a quintessential negative inhibitor of osteoclastogenesis and bone resorption. The functional mechanism involves its targeting of two osteoclast differentiation factors, calcitonin receptor (Calcr) and ephrin A receptor 2 precursor (EphA2) [84]. Recent experiments have shown that oleanolic acid, a new drug that can be used to treat osteoporosis, inhibits RANKL-induced osteoclastogenesis through the ERα/ miR-503/RANK signaling pathway in RAW264.7 cells [85].…”
Section: Microrna-mediated Mechanismsmentioning
confidence: 99%
“…miR-141 has been identified as a quintessential negative inhibitor of osteoclastogenesis and bone resorption. The functional mechanism involves its targeting of two osteoclast differentiation factors, calcitonin receptor (Calcr) and ephrin A receptor 2 precursor (EphA2) [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ephrin type-A receptor 2 (EphA2) is suggested to be a miR-141 target in rhesus monkey osteoclasts [ 52 ]. Excessive expression of EphA2 in OCPs induces osteoclast differentiation.…”
Section: Involvement Of Ncrnas In Osteoclast Differentiationmentioning
confidence: 99%
“…EphrinA2 expression is rapidly induced in a c-Fos-dependent manner and cleaved by metalloproteinases to release an active soluble form able to interact with its receptor EphA2, enhancing osteoclastogenesis (55). In rhesus monkey BMMs EphA2 is a potential target of miR-141 (56). OC differentiation and bone resorption are suppressed in vitro by miR-141, and in vivo using repeated injections of an OC-targeted delivery system into aged monkeys (56).…”
Section: Mirnas In the Early Phase Of Ocs Generationmentioning
confidence: 99%
“…In rhesus monkey BMMs EphA2 is a potential target of miR-141 (56). OC differentiation and bone resorption are suppressed in vitro by miR-141, and in vivo using repeated injections of an OC-targeted delivery system into aged monkeys (56). The calcitonin receptor (CALCR) is also a target of miR-141 in rhesus OCs.…”
Section: Mirnas In the Early Phase Of Ocs Generationmentioning
confidence: 99%